The politics of scale in global governance: do more stringent international forest certification standards protect local rights in Russia? - Tysiachniouk, MS; McDermott, CL; Kulyasova, AA; Teitelbaum, S; Elbakidze, M (Elsevier, 2021)
This paper interrogates how the increasing stringency of international rules on Free Prior and Informed Consent (FPIC), as reflected in the Forest Stewardship Council (FSC)’s certification standards, is shaping the rights afforded indigenous and local communities in Russia. Viewing the FSC as a ‘global governance generating network’ (GGN) that gains rule-making authority through diverse ‘forums of negotiation’ at multiple scales, we examine how international rules are negotiated and re-configured regarding 1) the ‘scope’ of requirements – who is included or excluded from FPIC and 2) ‘prescriptiveness' – the level and specificity of the rights afforded to FPIC holders.